1995
DOI: 10.1080/03079459508419092
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity among antisera raised against five avianEimeriaspecies in the natural host and in rabbits

Abstract: SUMMARYWater-and SDS-soluble antigens were prepared from purified sporulated oocysts of Eimeria acervulina, E. maxima, E. necatrix, E. praecox and E. tenella. Reactivity of . chicken hyperimmune anti-Eimeria sera, rabbit anti-oocyst and rabbit anti-sporozoite sera with the homologous and heterologous oocyst antigens were determined and cross-reactivities were expressed as a percentage of those homologous sera. The results demonstrated that the antisera from chickens infected naturally with Eimeria species d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The antibody titers from rabbits increased at 14 days PI, peaked at 28 days, and then declined slightly to reach a plateau. This is consistent with previous reports where antibodies persist for prolonged periods in birds and rabbits that have received continuous booster doses [ 7 , 10 , 44 , 45 ]. The pattern of the antibody response indicates a maturation affinity event.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The antibody titers from rabbits increased at 14 days PI, peaked at 28 days, and then declined slightly to reach a plateau. This is consistent with previous reports where antibodies persist for prolonged periods in birds and rabbits that have received continuous booster doses [ 7 , 10 , 44 , 45 ]. The pattern of the antibody response indicates a maturation affinity event.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with Talebi and Mulcahy [ 44 ], the increased titers of antibodies against Eimeria have a significant negative correlation with the oocyst output, Interestingly, we also observed an increase in antibody titers against E. tenella in our immunization/challenge trial. The antibody titers from rabbits increased at 14 days PI, peaked at 28 days, and then declined slightly to reach a plateau.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The antibody responses of chickens to Eimeria infections have been characterized with regard to parasite lifecycle stages, immunodominant antigens and dynamics (Xie et al, 1992;Smith et al, 1993;Tomley, 1994;Talebi and Mulcahy, 1995;Tajima et al, 2003;Onaga et al, 2005;Constantinoiu et al, 2007). However, most studies of the antibody responses reported to date have been conducted with wild-type strains that have not been subject to any selection.…”
Section: Introductionmentioning
confidence: 96%
“…Coccidiosis is one of the most common and problematic parasitic diseases in all classes of domestic animals caused by several species of coccidia (Tolebi and Mulcahy, 1995). It is a ubiquitous protozoan infection of animals seriously impairing their growth and food utilization (Abdel-Megeed et al, 2005) and causes significant mortality in domestic rabbits (Hauptman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%